Kurt Rothschild's Heterodox Approach to Price Theory and Oligopoly - Bloch, Harry; Bhattacharya, M. (History of Economic Thought Society of Australia, 2014)
The Seminal article by Kurt Rothschild on the state of imperfect competition analysis, 'Price theory and oligopoly', published in the Economic Journal in 1947 is used as an exemplar of the merits of a heterodox approach to economics. We identify key elements of Rothschild's analysis and relate them to later analytical developments in pricing strategies, entry barriers, internal organisation and the use of power by firms. Further, we note lacunae that remain in the modern analysis of oligopoly and price theory that can be addressed by adopting ideas proposed by Rothschild in his 19647 article and in his later writings.